Slang Language Used By Sissy Community - Heva Rostiana (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2016)
The objectives of this research are to find out kinds of slang language used by sissy. In this research, the researcher used a descriptive method. By using this method, the researcher aimed to describe slang language used by sissy. The populations are seven sissies in seven events and the samples are entire populations. Some of the researches findings are the words “Akikah, Eke, and Yey” occur most and contrary the other words occur least. They use slang language only in their community; on contrary they seldom use their language with their general society.